Customer Loyalty in Urban Restaurants: The Role of Experience and Atmosphere - Clara, Catharina; Irawan, Celesta; Sandra, Monaly (Business Economic, Communication, and Social Sciences Journal (BECOSS), 2025)
This study aims to investigate the influence of experiential marketing, store atmosphere, offline service quality, and electronic service quality on customer satisfaction and loyalty within the context of omnichannel urban restaurants in Indonesia. This study extends the S-O-R and ECT models by demonstrating how experiential and atmospheric cues outweigh functional digital factors in emerging market contexts. A quantitative method was employed, and data were collected through an online questionnaire distributed to customers who had experienced both online and offline services from urban restaurants. A total of 250 valid responses were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicate that customer satisfaction significantly affects customer loyalty, confirming its mediating role. Experiential marketing strongly influences both satisfaction and loyalty, emphasizing the importance of emotional and sensory engagement. Store atmosphere positively impacts satisfaction, underlining the role of physical environment in enhancing the dining experience. While offline service quality has a marginal effect on satisfaction, electronic service quality does not show a significant impact. These findings suggest that digital features alone are insufficient to generate emotional responses unless combined with meaningful physical interactions. Therefore, urban restaurant managers should prioritize integrated experiences that blend digital efficiency with memorable offline touchpoints. Future studies could examine moderating variables such as customer digital readiness or include constructs like trust or engagement to enrich the model. This study contributes to the growing literature on omnichannel customer experience by offering a comprehensive perspective that integrates both online and offline service quality into a unified satisfaction–loyalty framework.